Efektivitas Jus Terong Belanda dan Jus Tomat Terhadap Kadar Hemoglobin Ibu Hamil Trimester III - Munayarokh; Sinta Nur Rohmah; Sri Winarsih; Wahyu Joko Saputra (2024)
The purpose of this study is to determine the effectiveness of eggplant juice and tomato juice on hemoglobin levels of pregnant women in the third trimester.This research was conducted in the working area of the Kandangan Health Center.This study uses a Quasi Experiment with a two-group pretest-posttest without control approach. A sample of 36 pregnant women in the third trimester. The sampling technique is a non-probability sampling approach with purposive sampling. The data normality test uses the Shapiro Wilk test. Data analysis of 2 unpaired groups using the T-Test Independent test.The results of the study showed that Dutch eggplant juice was not more effective on hemoglobin levels of pregnant women in the third trimester than tomato juice.The mean rank results in the Dutch eggplant juice group were 0.378 gr/dL and in the tomato juice group were 0.683 gr/dL, while the results of the analysis using the Independent T Test test obtained a p value of 0.116 > α 0.05 and the results of the t calculation obtained a ttable < tcount or 1,613 < 2,028, it can be concluded that Dutch eggplant juice is not more effective on hemoglobin levels of pregnant women in the third trimester than tomato juice.